Horrid Henry - Simon Francesca 1955-; Francesca Simon (Britain : Orion Children's Books, 1994)
Horrid Henry causes his brother Perfect Peter all sorts of problems when he behaves properly for a change, upstages Peter at a dance recital, plays pirates, and goes on a camping trip.
K
550